Simulation of biaxial wheel test and fatigue life estimation considering the influence of tire and wheel camber. (February 2016) - Wan, Xiaofei; Shan, Yingchun; Liu, Xiandong; Wang, Haixia; Wang, Jiegong
Highlights: Camber status and stress distribution of wheel under biaxial loads are analyzed according to the standard EUWA ES 3.23. Fatigue life of the wheel is estimated using stress life (S-N) method based on the stress analysis of the wheel. The comparison is conducted between the simulation results of biaxial wheel fatigue test and uniaxial fatigue test, and the results validate the stringency and practicality of the standard. Abstract: The traditional fatigue test of wheel comprising the radial and cornering fatigue tests cannot simulate the real stress state of wheel well. Biaxial wheel fatigue test combining these two traditional tests has become an internationally recognized method that can reproduce the real loading condition of the wheel in service. Since the test is time- and cost-consuming, developing the simulation method on biaxial wheel fatigue test is urgently necessary. In this paper, a new method is proposed to evaluate the fatigue life of commercial vehicle wheel, in which the finite element model of biaxial wheel fatigue test rig is established based on the standards of EUWA ES 3.23 and SAE J2562, and the simulation of biaxial wheel test and fatigue life estimation considering the effects of tire and wheel camber is performed by applying the whole load spectrum specified in ES 3.23 to the wheel. The radial and cornering fatigue tests are also simulated, and the results are compared with ones of the biaxial fatigue test. The research shows that the proposed method provides an efficient tool for predicting the fatigue life of the wheel in the biaxial fatigue test.